2022
DOI: 10.1186/s12884-022-04747-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum ultrasound measurement of the lower uterine segment thickness in parturients with previous scar in labor: a cross-sectional study

Abstract: Background There is a lack of reliable methods to estimate the risk of uterine rupture or dehiscence during a trial of labor in women with previous cesarean sections. This study aimed to assess the lower uterine segment and myometrial thickness by ultrasonography in women with previous cesarean sections during labor and assess their association with the uterine defect. Methods A cross-sectional study was conducted on 161 women in the active phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, a full LUS thickness of 2.3 mm in women during the first stage of labor is associated with a high risk of complete uterine rupture during a trial of labor. We believe that measuring the full thickness of the LUS may be of practical use when deciding on the mode of delivery and may lead to a reduction in the incidence of uterine ruptures [24]. Despite the high predictive value of this measurement, in our case, it did not protect the patient from uterine rupture.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, a full LUS thickness of 2.3 mm in women during the first stage of labor is associated with a high risk of complete uterine rupture during a trial of labor. We believe that measuring the full thickness of the LUS may be of practical use when deciding on the mode of delivery and may lead to a reduction in the incidence of uterine ruptures [24]. Despite the high predictive value of this measurement, in our case, it did not protect the patient from uterine rupture.…”
Section: Discussionmentioning
confidence: 55%
“…According to Alalaf et al, there is a greater probability of uterine defects during a labor trial if the first stage of labor is characterized by a lower uterine segment thickness of 2.3mm and a myometrial thickness of 1.9mm. The body mass index, birth weight, inter-delivery interval, mother age, or gestational age at labor did not correlate with the uterine defects [16] .…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies by us 34 and He et al 35 found that lower uterine segment thickness reduction was associated with uterine rupture and TOLAC failure in women who underwent planned cesarean delivery. Sonography of the lower uterine segment in the pregnancy interval or first trimester, 36 before labor, 34 or during labor 37 have been reported, together with a standardized ultrasonic evaluation and reporting system for cesarean delivery scar pregnancy in the first trimester 38 . It could be an option to also measure the lower uterine segment or scar before and during labor as an independent prediction factor.…”
Section: Discussionmentioning
confidence: 99%